Luminescent copper indium sulfide (CIS) quantum dots for bioimaging applications. Issue 9 (15th July 2021) - Morselli, Giacomo; Villa, Marco; Fermi, Andrea; Critchley, Kevin; Ceroni, Paola
Abstract : This review covers the main applications of copper indium sulfide quantum dots for bioimaging applications. Abstract : Copper indium sulfide (CIS) quantum dots are ideal for bioimaging applications, by being characterized by high molar absorption coefficients throughout the entire visible spectrum, high photoluminescence quantum yield, high tolerance to the presence of lattice defects, emission tunability from the red to the near-infrared spectral region by changing their dimensions and composition, and long lifetimes (hundreds of nanoseconds) enabling time-gated detection to increase signal-to-noise ratio. The present review collects: (i) the most common procedures used to synthesize stable CIS QDs and the possible strategies to enhance their colloidal stability in aqueous environment, a property needed for bioimaging applications; (ii) their photophysical properties and parameters that affect the energy and brightness of their photoluminescence; (iii) toxicity and bioimaging applications of CIS QDs, including tumor targeting, time-gated detection and multimodal imaging, as well as theranostics. Future perspectives are analyzed in view of advantages and potential limitations of CIS QDs compared to most traditional QDs.